STRATEGI KOMUNIKASI PEMASARAN UMKM JAMU SWEGERR REKK DI KOTA PALEMBANG - Syafitri, Elvina Nadia; Maharani, Dwi (Jurnal Riset Mahasiswa Dakwah dan Komunikasi, 2025)
This study aims to examine the marketing communication strategy implemented by the MSME Jamu Swegerr Rekk in Palembang City in addressing market challenges, leveraging digital opportunities, and building customer trust. Using a qualitative descriptive approach, data were obtained through observation, in-depth interviews, and documentation with business owners and regular customers. The results show that Jamu Swegerr Rekk applies the 4P marketing mix (Product, Price, Place, Promotion) with an emphasis on communication strategies via social media and community events. The main obstacle lies in the absence of a BPOM distribution permit, affecting both distribution and consumer trust. This study recommends the need to strengthen product legality, optimize digital media, and collaborate with formal institutions to enhance positioning and competitiveness.